Laboratory transmission of an Asian strain of Leishmania tropica by the bite of the southern European sand fly Phlebotomus perniciosus. Issue 6 (May 2019) - Bongiorno, Gioia; Di Muccio, Trentina; Bianchi, Riccardo; Gramiccia, Marina; Gradoni, Luigi
Graphical abstract: Highlights: Imported cases of anthroponotic cutaneous leishmaniasis due to Leishmania tropica are increasingly documented in Europe. Vector competence for an Asian L. tropica was investigated in Phlebotomus perniciosus, a southwestern European sand fly. Leishmania tropica developed into abundant metacyclic promastigotes in 20% of laboratory-infected P. perniciosus. Parasites have been successfully transmitted from infected to naive hamsters by the bite of P. perniciosus. In particular settings P. perniciosus, a Leishmania infantum vector, may play the role of an occasional L. tropica vector. Abstract: Imported cases of anthroponotic cutaneous leishmaniasis due to Leishmania tropica are increasingly documented in Europe. We investigated the ability of Phlebotomus perniciosus, a competent vector of Leishmania infantum widespread in southwestern Europe, to support the growth and transmissibility of an Asian strain of L. tropica recently isolated from a refugee. Parasite growth behavior was investigated in laboratory-reared sand flies fed artificially with promastigotes as well as in sand flies infected after biting on footpad lesions induced in hamsters by promastigote inoculation. The evolution of infection was checked by gut microscopy and quantitative real-time PCR, and it was found to be similar between promastigote- and amastigote-initiated infections. In 80% of infected sand flies, despite survival and flourishing growth of promastigotes after blood digestion and defecation, either the parasites died, or failed to migrate to the foregut and/or to mature into infective forms. However, in the remaining 20% L. tropica developed into abundant metacyclic promastigotes. The quantitative real-time PCR assay detected variable loads of gut promastigotes irrespective of morphological evidence of viability or progressive/final death. Parasite transmissibility was investigated by exposing naive hamsters to P. perniciosus previously infected on chronic lesions induced in hamsters which survived to take a second blood meal. Two months post exposure, lesions developed in skin sites bitten by sand flies confirmed to harbor metacyclic promastigotes; in the following months, the presence of viable and transmissible L. tropica parasites in lesions was demonstrated by xenodiagnosis assays. Our findings support the hypothesis that, in particular epidemiological situations, P. perniciosus may play the role of an occasional L. tropica vector.